The Three Dimensional Spiral of Sense: A New Paradigm Systemic Applied a Six Areas Disciplinares and Two Axis: Identity and Professionalization (European Journal of Formal Sciences and Engineering, 2023)
This article introduces a new systemic theory called “The Three Dimensional Spiral of Sense”, applied to Identity and Professionalization. The epistemological mainstays of the theory are stressed here, a theory supported by more than 30 years of empirical research at CONICET (National Council of Scientific Research, Argentina), with individuals belonging to different populations, some of them covering periods of over 20 years (intra-generational studies), and others covering three generations in-line (inter-generational studies). This article presents the most specific theoretical frameworks, and it formulates the six disciplinary areas in which the new analysis of the social data was carried out: Education, Health, Science, Media, International Relations and Interculturality. The first area – Education – is dealt with through different levels (secondary level, tertiary level, University and PhD training. Here, we only make reference to the studies carried out, returning to some epistemological issues in this theory. The methodology used was quantitative (statistical analysis, a semi-structured survey) but mainly qualitative (hierarchical evocations, interviews). The approach was macro-micro-meso-macro, micro, not quite common yet. It consists of a kind of sui generis systemism which recovers relationships (links, back and forth) between individuals and contexts, without overlooking neither the former nor the latter, thus, avoiding any type of reductionism. Individuals, organizations and frameworks interplay and feedback themselves. The results, particularly the qualitative ones, show the rich interactions underlying the continuance or innovation processes, which favor or hinder the individuals’ development and identity in times of abrupt change; at the same time, these results reveal the need for Professionalization in emerging countries.
Keywords: Systemic Sui Generis Paradigm, the Theory of the Three-Dimensional Spiral of Sense, Identity, Professionalization